Brominated flame retardants: a novel class of developmental neurotoxicants in our environment? - Eriksson, P (2001)
Brominated flame retardants are a novel group of global environmental contaminants. Within this group the polybrominated diphenyl ethers (PBDE) constitute one class of many that are found in electrical appliances, building materials, and textiles. PBDEs are persistent compounds that appear to have an environmental dispersion similar to that of polychlorinated biphenyls (PCBs) and dichlorodiphenyltrichloroethane (DDT). Levels of PBDEs are increasing in mother's milk while other organohalogens have decreased in concentration. We studied for developmental neurotoxic effects two polybrominated diphenyl ethers, 2,2',4,4'-tetrabromodiphenyl ether (PBDE 47) and 2,2',4,4',5-pentabromodiphenyl ether (PBDE 99)--congeners that dominate in environmental and human samples--together with another frequently used brominated flame retardant, tetrabromo-bis-phenol-A (TBBPA). The compounds were given to 10-day-old NMRI male mice, as follows: PBDE 47, 0.7 mg (1.4 micromol), 10.5 mg (21.1 micromol)/kg body weight (bw); PBDE 99, 0.8 mg (1.4 micromol), 12.0 mg (21.1 micromol)/kg bw; TBBPA, 0.75 mg (1.4 micromol), 11.5 mg (21.1 micromol)/kg bw. Mice serving as controls received 10 mL/kg bw of the 20% fat emulsion vehicle in the same manner. The present study has shown that neonatal exposure to PBDE 99 and PBDE 47 can cause permanent aberrations in spontaneous behavior, evident in 2- and 4-month-old animals. This effect together with the habituation capability was more pronounced with increasing age, and the changes were dose-response related. Furthermore, neonatal exposure to PBDE 99 also affected learning and memory functions in adult animals. These are developmental defects that have been detected previously in connection with PCBs.